Comparative Analysis of International and Malaysian Legal Frameworks On The Treatment On Uncontrollable Children: Is There Any Inconsistency? - Mohamad Kamal Sodiqin Abdull Manaf (USIM Press, 2024)
Malaysian Journal of Syariah and Law ol. 11, No.1, Page (1-13)